Utilizing Teams Games Tournament in Teaching Reading to Enhance Students’ Comprehension on Narrative Texts - Septiana, Tri Ilma (Universitas Lambung Mangkurat, 2023)
The present study has the main objective to test whether the Teams Games Tournament (TGT) method can improve students' reading comprehension on narrative texts. To answer the formulation of the problem, this study utilized a quasi-experimental method by involving an experimental class and a control class with data collection techniques through observation, reading comprehension test, and interviews. The results of this study reveal three main points: First, a comparison between the results of the t-test and t-table at a significant level of 5% showed tt > t0 or 9.13 > 1.67. This means that the Teams Games Tournament can enhance students' reading comprehension on narrative texts. Second, the TGT method can increase student cooperation, train courage to express opinions, build discipline, caution, and tolerance towards fellow students. Third, this method can also create a competitive learning climate and encourage students to become active learners.